Investigation on beneficiation of goethite-rich iron ores using reduction roasting followed by magnetic separation. Issue 3 (3rd July 2019) - Ravisankar, Vivek; Venugopal, R.; Bhat, Harikrishna
ABSTRACT: In this study, reductive roasting followed by low-intensity magnetic separation were used to upgrade iron ore from Gua mines in Jharkhand. The work aimed to maximise the recovery of iron values by upgrading to a high-grade product suitable for pelletisation and sintering. The received ore contains 58% Fe, 7.82% silica, 4.26% alumina and 4.97% loss on ignition. Reductive roasting experiments were conducted at times of 10, 20 and 30 min at 600°C, 700°C and 900°C using coal as a reducing agent. Roasted samples were processed using a low-intensity magnetic separator. Best results were obtained at 800°C for 30 min using 10% coal in the charge. Using these conditions a product containing 66.6% Fe was produced at 90.4% recovery. The roasted samples were characterised by XRD which confirms the hematite to magnetite transformation and by SEM which highlighted the porous nature of the upgraded ore. GRAPHICAL ABSTRACT: